PEMILIHAN TEMAN KOS PADA MAHASISWA PENDATANG DI KOSAN EMPAT DARA DI BANGAU SAKTI - Wibowo, Bagus Tri; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The research was conducted at Kosan Empat Dara In Bangau Sakti. The purpose of this study is to determine the factors that affect the selection of friends in one boarding house. The focus of this research is to form the social relations of friends in one boarding house. The technique of determining samples by census or survey and assigning a total sample of 40 people. The writer uses quantitative descriptive method and Instrument data is observation, questionnaire and documentation. The study found that there are several factors that determine the selection of boarding buddies on the respondents in Kosan Empat Dara In Bangau Sakti, namely as follows: Lifestyle Similarity, the study found that respondents chose buddy one more influenced by the similarity of hobby and other similarity activities (77.5% ), Similarity of Place of Origin, Research also found that respondents make characteristic of origin region (40,0%) as determinant factor buddy one boarding. In addition, tribal factors did not affect the preferences of respondents in determining buddies one kos (100.0%). Personal Attachment, Research finds that respondents consider the personality of one's friends to see if the peers can be used as friends when ngekos together or not. However, these factors are not too (16.0%) affect the preferences of students in choosing friends kos. Keywords: Social Relations, Peer Friends Preference